Cytokine expression in rhinovirus- vs. respiratory syncytial virus-induced first wheezing episode and its relation to clinical course - Komulainen, Miisa (My University, 2023)
Rhinovirus (RV) and respiratory syncytial virus (RSV) are usual causes of common cold and bronchiolitis. Bronchiolitis is described as a virus-induced inflammation of small bronchioles with the clinical characteristic of expiratory breathing difficulty in children under 2 years. It has been suggested that bronchiolitis as a diagnosis is not specific enough and needs classification according to the type of viral infection. Unlike RSV, RV-induced bronchiolitis is associated with markedly increased risk of asthma. Our goal was to investigate the cytokine profiles of RV- and RSV-induced first wheezing episode and their correlation to prognosis. 52 children with sole RV- and 11 with sole RSV-infection in need of hospitalization due to bronchiolitis were recruited. Peripheral blood mononuclear cells (PBMCs) were isolated during acute illness and 2 weeks later. PBMCs were stimulated in vitro with anti-CD3/anti-CD28 for 24 hours. The expression levels of 56 cytokines were analyzed by multiplex ELISA. Virus diagnostics were done with PCR from a nasopharyngeal sample and sensitization was tested by allergen specific IgE from blood serum. Recurrent wheezing and development of asthma were prospectively followed for 4 years. We found statistically significant differences between cytokine responses from PBMCs in RV- and RSV-induced first wheezing episode, especially in the acute phase. While, in the RV group, the expression levels of Type 2 cytokines were higher, in the RSV group Type 1 cytokines as well as proinflammatory-associated cytokines were expressed more. The RV group was characterized by decreased expression of interleukin 1 receptor antagonist (IL-1RA), interleukin 1 beta (IL-1b), and monocyte chemoattractant protein-1 (MCP-1) and increased expression of eosinophil chemotactic protein 2 (eotaxin-2), thymus- and activation-regulated chemokine (TARC), and epithelial-derived neutrophil-activating peptide 78 (ENA-78) in the acute phase compared to those in the RSV group. Several different cytokines, such as interferon gamma (IFN-g), macrophage-derived chemokine (MDC), IL-1RA, and vascular endothelial growth factor (VEGF), classified in a wide range of functional groups, were connected to a shorter duration of hospitalization in the RSV group. These findings reveal new potential biomarkers for short- and medium-term prognoses in high-risk children, however, further trials are warranted.

Rinovirus (RV) ja respiratory syncytial virus (RSV) ovat yleisimpiä patogeenejä hengitystieinfektioiden ja akuutin bronkioliitin taustalla. Bronkioliitti määritellään viruksen aiheuttamaksi pienten keuhkoputkien tulehdukseksi, jonka pääoireena on akuutti uloshengitysvaikeus. Bronkioliitin ikäkriteereissä on kansainvälistä vaihtelua, yläikäraja ulottuu kahteen ikävuoteen. Bronkioliitin määritelmän on esitetty olevan epätarkka ja on ehdotettu bronkioliitin jaottelua virusetiologian mukaan. Rinovirusetiologia bronkioliitissa on yhdistetty lapsuusiän astman merkittävästi lisääntyneeseen riskiin, kun taas RS-viruksella tätä ei ole havaittu. Tavoitteenamme oli tutkia eroja sytokiinipitoisuuksissa rino- ja RS-viruksen välillä lapsen ensimmäisessä uloshengitysvaikeuskohtauksessa. Tutkimukseen rekrytoitiin akuutin uloshengitysvaikeuden vuoksi sairaalahoitoa tarvitsevia lapsia, joista 52:lla todettiin RV- ja 11:llä RSV-infektio. Potilailta otettiin verinäytteet, joista eristettiin perifeerisen veren mononukleaarisia soluja. Mononukleaarisia soluja stimuloitiin anti-CD3/antiCD28-aktivaattorilla in vitro. Yhteensä 56:n sytokiinin pitoisuudet analysoitiin Multiplex-ELISApaneelilla. Virusetiologia määritettiin PCR:llä nenänielunäytteestä ja herkistyminen tietyille allergeeneille veren seerumin IgE-pitoisuudella. Astman ja toistuvan uloshengitysvaikeuden kehittymistä seurattiin neljän vuoden ajan. Ensimmäisen uloshengitysvaikeuskohtauksen yhteydessä sytokiinipitoisuuksissa havaittiin merkitseviä eroja rino- ja RS-viruksen välillä erityisesti akuuttivaiheessa. Rinovirusinfektiossa havaittiin enemmän tyypin 2 sytokiiniaktiivisuutta, kun taas RS-virusinfektiossa enemmän tyypin 1 aktiivisuutta sekä proinflammatorisia sytokiineja. Etiologioiden välisiä sytokiiniprofiileja verrattaessa akuuttivaiheessa rinovirukseen liittyi matalampi interleukiini-1-reseptorin salpaaja (IL1RA) - ja kemokiiniligandi-2 (MCP-1) -pitoisuus ja korkeampi kemokiiniligandi-24 (eotaxin-2) -, kemokiiniligandi-17 (TARC) - ja CXCL5-kemokiini (ENA-78) -pitoisuus. Sytokiinipitoisuuksien ja sairaalahoidon pituuden välillä oli yhteys RS-viruspotilailla mutta ei rinoviruspotilailla. Tutkimuksemme tarjoaa uusia mahdollisia merkkiaineita korkean riskin potilaiden ennusteen arvioimiseen, mutta jatkotutkimusta tarvitaan.
Keywords: rhinovirus, respiratory syncytial virus, bronchiolitis, cytokine